2008
DOI: 10.1007/s10680-008-9160-z
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Women in Consanguineous Marriages in Egypt, 1988–2000

Abstract: This article reviews three mechanisms related to autonomy, wealth, and local cultural factors, which are said to underly the high prevalence of consanguineous marriage in Arab societies. It then assesses each of them empirically in two stages. The first uses a pooled dataset constituted by the most recent marriage cohorts in the 1992 and 2000 waves of the Egyptian Demographic and Health Surveys. Three results stand out. The frequency of consanguinity in the most recent marriage cohorts (i) is strongly correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 33 publications
2
44
0
Order By: Relevance
“…A complementary possible explanation for the lower ages of marriage found in the exogamous community families Table 4 Regression results for 1st model specification. end of the spectrum Iraq, Jordan, Kuwait, Pakistan, Saudi Arabia and the UAE demonstrate a level of endogamous marriages of over 50% (Weinreb, 2008). Why does endogamy remain an attractive prospect despite the well-documented possibilities of inbreeding and lowered immunity?…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A complementary possible explanation for the lower ages of marriage found in the exogamous community families Table 4 Regression results for 1st model specification. end of the spectrum Iraq, Jordan, Kuwait, Pakistan, Saudi Arabia and the UAE demonstrate a level of endogamous marriages of over 50% (Weinreb, 2008). Why does endogamy remain an attractive prospect despite the well-documented possibilities of inbreeding and lowered immunity?…”
Section: Resultsmentioning
confidence: 99%
“…In a simplified vision of the world, Islamic societies are noted for their marked private/public dichotomy, when it comes to the authority of the women, and for the creation of distinct social spaces for the different sexes. This entails that women have a degree of power and freedom of movement within their own homes but when it comes to the outside world this power and freedom is diminished (Weinreb, 2008). This view of Islamic societies is an oversimplification; one which must be nuanced by noting that agency of women is affected by their generational standing (e.g., if they are mothers or mothers-in laws), their education and their social class.…”
Section: Islamic Marriagementioning
confidence: 99%
“…Using data from several countries, studies have found high rates of consanguineous unions to be generally prevalent in poor traditional rural areas where women get married at younger ages, are less educated, and are less likely to be participate in economic activities (Bittles, 1994;Shah, 2004;Weinreb, 2008).…”
Section: Consanguineous Marriagementioning
confidence: 99%
“…Studies have speculated on social and economic benefits. Social benefits include lower spousal search costs, greater compatibility between spouses, a closer relationship between the bride and her in-laws, higher social status for the family, greater autonomy for women, as well as the lower likelihood of divorce (Bittles, 1994;Hussain, 1999;Weinreb, 2008;Sandridge et al, 2010). On the other hand, economic factors include lower dowry or bride price payments at the time of marriage, greater control of financial assets for women, and larger female inheritance (Reddy, 1988;Bittles, 1994;Weinreb, 2008).…”
Section: Consanguineous Marriagementioning
confidence: 99%
“…Another important element that has a significant influence on fertility and mortality rates is (un)employment, let alone its role in defining the economy of the society and the level of poverty (Bildirici et al, 2009). Early marriage and marriage among relatives are also significant, as they influence not only the socioeconomic status, but also the society's mortality rates (Bildirici et al, 2009;Othman and Saadat, 2009;Weinreb, 2008).…”
Section: Introductionmentioning
confidence: 99%